Analisis Kepuasan Pasien Terhadap Kualitas Pelayanan Umum di Klinik Cipinang Jakarta dengan Metode Servqual - Harminto Harminto; Wahju Inggar Fipiana; Vivi Lusia (Jurnal Manajemen FE-UB, 2021)
Service suitability is very influential on patient safety because in carrying out medicalactions must be adjusted to the Medical Service Standards in order to increase customersatisfaction, for that the author conducted a study entitled Analysis of Patient Satisfaction on theQuality of Public Service at Klinik Cipinang Jakarta, and the method used is the method servqual.This method makes a comprehensive assessment of customer satisfaction for services in the healthsector. Assessment is carried out on 5 dimensions of service quality;reliability, responsiveness,assurance, empathy, tangibles. Data were obtained from the distribution of questionnaires to 100patients as respondents using simple random sampling technique. This study obtained a numberof 31 attributes of customer needs, which are divided into 8 attributes on the aspect of reliability,5 attributes on the aspect of responsiveness, 5 attributes of assurance, 5 attributes on thedimension of empathy, and 8 attributes on the dimension of tangibility. This study concludes thatthere is a gap between expectations and the quality of services provided, with the main focus thatneeds to be improved: doctors come on time, nurses are ready to serve patients at all times, andnurses are educated and able to serve patients. Although the services provided are not fully asexpected, the quality of Klinik Cipinang Jakarta's services is good enough and needs to beimproved.Keywords: Service Quality, Servqual